The impact of quality of work life (QWL) and work motivation on the organizational citizenship behavior (OCB) with job satisfaction as a mediating variables - Nur Hidayah; Hidajat Hendarsjah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aims to determine the impacts of Quality of World Life (QWL), Work Motivation (WM) on Organizational Citizenship Behavior (OCB) mediated by Job Satisfaction (JS). Here, information and data are obtained from 171 responses from PT. Regar sport Industri Indonesia employees collected using online questionnaires. The data were analyzed via factor analysis with SPSS supports. From the analysis, the results describe that there is a direct effect of QWL and WM on OCB. Furthermore, there is an indirect influence of QWL and WM on OCB mediated by JS. Interestingly, the mediation variable is incapable to directly affect the OCB.  Therefore, this study demonstrates the importance of QWL and motivation so that Job Satisfaction is fulfilled and finally the formation of OCB employees is established.